2013
DOI: 10.1007/s10162-013-0390-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Sensitivity to Broadband Binaural Localization Cues in the Ferret

Abstract: Although the ferret has become an important model species for studying both fundamental and clinical aspects of spatial hearing, previous behavioral work has focused on studies of sound localization and spatial release from masking in the free field. This makes it difficult to tease apart the role played by different spatial cues. In humans and other species, interaural time differences (ITDs) and interaural level differences (ILDs) play a critical role in sound localization in the azimuthal plane and also fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 55 publications
(92 reference statements)
5
27
0
Order By: Relevance
“…This value is comparable to reports in rabbit (50-60 µs, Ebert et al 2008), ferret (23 µs, Keating et al 2013), and cat (~30 µs, Wakeford and Robinson 1974). By assuming guinea pigs have a similar ITD discrimination threshold of 55 µs, and taking into account the average ITD slope of 3 µs/º reported here, we can predict a low-frequency spatial discrimination ability of 18.3º, slightly broader than reported in chinchilla.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This value is comparable to reports in rabbit (50-60 µs, Ebert et al 2008), ferret (23 µs, Keating et al 2013), and cat (~30 µs, Wakeford and Robinson 1974). By assuming guinea pigs have a similar ITD discrimination threshold of 55 µs, and taking into account the average ITD slope of 3 µs/º reported here, we can predict a low-frequency spatial discrimination ability of 18.3º, slightly broader than reported in chinchilla.…”
Section: Discussionsupporting
confidence: 89%
“…However, by analyzing the range of cues available to guinea pig, and comparing these values to other similar species, we can make some conservative predictions regarding the behavioral ability of guinea pig in localizing and discriminating sounds in space. Previous studies have shown minimum ILD discrimination in humans, primates, cats and ferrets between 1–4 dB (Houben and Gourevitch 1979; Keating et al 2013; Mills 1960; Scott et al 2007; Wakeford and Robinson 1974) (see Tsai et al 2010 for review). Similarly, consideration of acoustic measurements from our lab (Koka et al 2011) along with psychophysical data (Heffner et al 1994) suggest that chinchillas should be able to discriminate ILDs of at least 4 dB, which coincides with the 13.7º spatial acuity reported by Heffner et al (1994) for broadband noise high-pass filtered at 8 kHz.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral ILD sensitivity is consistent with several-millisecond windows of E-I interaction Previous psychophysical measurements in human (Hartmann and Constan, 2002) and animal subjects (Egnor, 2001;Keating et al, 2013) indicated that psychophysical detection of ILDs was essentially unaffected by decorrelation. These experiments used broadband stimuli that conveyed information in many auditory filters simultaneously and did not assess the usability of suprathreshold information (e.g., for lateralization).…”
Section: Discussionmentioning
confidence: 63%
“…While chinchillas were selected for the audiometric similarity to humans, including a similar range of hearing (Heffner and Heffner, 1991) and demonstrated use of both ITD and ILD cues for sound localization (Heffner et al, 1994), such cross-species comparisons are, of course, limiting. The effect of interaural decorrelation on ILD sensitivity appears to be similarly negligible in humans (present study; Hartmann and Constan, 2002) and ferrets (Keating et al, 2013), and also barn owls (Egnor, 2001), but behavioral data from chinchilla or other animal models could be informative, if only to further confirm the lack of an effect. Although aspects of our behavioral and midbrain neural data were similar, other explanations for integrative ILD sensitivity (e.g., involving downstream mechanisms we did not consider) could certainly be proposed (Stecker et al, 2015).…”
Section: Origins Of Long Binaural E-i Windows In Iccmentioning
confidence: 85%
See 1 more Smart Citation